Pelatihan Seni Ecoprinting: Membawa Desa Sukaraharja ke Dunia Mode Ramah Lingkungan - Susanto, Laela; Arhasy, Aneu Nurkhalifah; Nurkarim, Syamsu; Rakista, Putri Mutiara (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
This activity was carried out in Sukaraharja village, which has a lot of plant potential to be used as material for making eco-prints. The purpose of this service is to enable the villagers to use the potential of the plants in the environment and at the same time increase the family income, which ultimately improves the economy of the residents. The method used in this service activity is direct practice in the production of ecoprint, which is carried out in the Sukaraharja. The stages of this activity include training on how to make ecoprint batik, starting with the presentation of materials and continuing with hands-on practice. Through this activity, it is expected that the community will gain insight and skills in using and creating the potential around their place of residence to make eco-print fabrics. It is also hoped that this activity will boost the village economy by creating new jobs. With these business opportunities, it is hoped that eco-print products can be favored and loved by the wider community and provide employment opportunities for the community to produce works that can be applied with eco-print.